Docking of New Designed Compounds Derived from 1,6-Dihydro-1,3,5-triazine-2,4-diamine Toward Quadruple Mutant Plasmodium Dihydrofolate Reductase - Imam Siswanto; Harno Dwi Pranowo; Mudasir Mudasir (Indonesian Journal of Chemistry, 2019)
Resistance to the traditional antifolates is now widespread in Plasmodium falciparum and Plasmodium vivax. To find the interaction model of some compounds derived from 1,6-dihydro-1,3,5-triazine-2,4-diamine, molecular docking technique was carried out using these compounds ligand and pDHFR as the receptor. Complex ligand and the receptor from Protein Data Bank (PDB ID 1J3K) were chosen as an interaction model between a ligand and its receptor. Each compound was optimized using ab initio methods with 6-311G basis set. Partial charges of ligand were added using AM1-BCC methods. Each ligand was docked to the receptor utilizing Dock6 software. Theoretical prediction based on the binding energy between these compounds as the ligand with pDHFR as receptor resulted in 1 compound, namely 6,6-dimethyl-1-[3-(2-chloro-4,5-dibromophenoxy)propoxy]-1,6-dihydro-1,3,5-triazine-2,4-diamine possessing binding affinity better than that of WR99210 which was known to have good antimalarial activity.